Editorial: Universities as Thinking Spaces for Society: Moving from Welfare to Development - Olajumoke Ogunsanya; Emem Anwana; Nolwazi Dlamini (African Journal of Inter-Multidisciplinary Studies, 2024)
South Africa's developmental challenges offer a fertile ground for collaborative efforts among various stakeholders, including higher education institutions, government bodies, industries, and civil society organizations. Such collaboration fosters channels for knowledge generation, opportunities for resource sharing, and strategies for policy enhancement, all aimed at driving South Africa's progressive transformation through its development agenda. This special issue is the result of a partnership between the Faculty of Management Sciences at Durban University of Technology, South Africa, and the Population Promotion Directorate of the KwaZulu-Natal Provincial Department of Social Development in South Africa. This special issue serves as a concerted effort to cultivate interdisciplinary collaboration between government institutions and universities, aiming to generate knowledge for the betterment of citizens' lives. As such, the papers within cover a range of themes addressing significant issues within South African society. Their findings are intended to serve as credible inputs for the development and implementation of policies in relevant domains. Utilizing both qualitative and quantitative data, these papers offer deeper insights into their respective subject matters, contributing to evidence-based policymaking and decision-making processes across various levels of government in South Africa.